Strategy of Energy for Commercial Building - Rewlay-ngoen, Chantima (Food Agricultural Sciences and Technology, 2020)
Presently, the average temperature in Thailand is tended to be increasing every year. Many organizations, therefore, create energy-saving campaigns to decrease energy consumption in buildings, for example, reduce unnecessary energy use, turn off all lights and switch off all electrical appliances when not in use, and reduce heat transfer in buildings. Reducing heat transfer in buildings is one of the energy-saving strategies that can decrease energy consumption. To study energy reduction by this strategy, this research aims to analyze Overall Thermal Transfer Value (OTTV) and Roof Thermal Transfer Value (RTTV) of a two-story commercial building. Construction materials data of the commercial building, such as walls and roofs, including temperature inside and outside of the commercial building, are collected to examine the study. According to the research, averages of OTTV and RTTV are 80.36 W/m2 and 59.18 W/m2 subsequently, which are higher than the standard values specified by the Ministry of Energy. By this, the commercial building would be needed for renovation in order to meet the standards. Adding insulation and gypsum board to wall, applying window tinted film, and attaching insulation and insulated ceiling to the roof can help to decrease the averages of OTTV and RTTV about 57% and 80% respectively. The outcomes from this research could be applied for the energy-efficient renovation of buildings in the future.